HISTOPATHOLOGICAL EFFECTS OF PAPER MILL EFFLUENT IN THE KIDNEY OF FRESHWATER FISH, LABEO ROHITA (HAM.) - TYOR, A.; PAHWA, K.; KAUR, S. (Journal of the Inland Fisheries Society of India, 2021)
The present study was conducted to assess the histopathological changes induced in the kidney of freshwater fish, Labeo rohita (Hamilton) exposed to different levels of paper mill effluent (PME) i.e. 10%, 15% and 25%; and a group of fish without exposure to effluent which served as control. Heavy metal analysis of the effluent was done by PerkinElmer Atomic Absorption Spectrophotometer (GBC 932A). The parallel use of light microscopy and transmission electron microscopy depicted various histopathological degenerative changes in the kidney exposed to different concentrations of PME viz. renal tubule degeneration, narrowing of tubular lumen, degeneration and shrinkage of glomerulus, change in shape of nucleus, rupture of nuclear membrane, condensation of chromatin material, fragmentation and blebbing of nuclear material, change in shape of mitochondria, degeneration of mitochondrial cristae, degeneration of mitochondrial membrane, occurrence of pleomorphic mitochondria, occlusion of tubular lumen and cytoplasmic vacuolization.Key words: Paper Mill Effluent, pleomorphic, renal tubule.